2019
DOI: 10.3857/roj.2019.00577
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in intensity-modulated radiation therapy use in Korea

Abstract: We aimed to analyze the trend in intensity-modulated radiation therapy (IMRT) use in Korea from 2011 to 2018. Materials and Methods: We collected data from the Health and Insurance Review and Assessment Service (HIRA) big data based on the National Health Insurance Service claims and reimbursements records using primary treatment planning codes (HD 041) for IMRT from 2011 to 2018. We analyzed the changing patterns in clinical application to specific tumor sites and regional differences in IMRT utilization. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…According to the Japanese Society for Radiation Oncology database report of 2018, IMRT was mostly used to treat prostate, head and neck, and central nervous system tumors in Japan [17]. However, in Korea, IMRT was most commonly used to treat breast, lung, and prostate cancers in 2018 [13]. JHIS adopted stricter indications for proton and carbon ion therapy ( Table 7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the Japanese Society for Radiation Oncology database report of 2018, IMRT was mostly used to treat prostate, head and neck, and central nervous system tumors in Japan [17]. However, in Korea, IMRT was most commonly used to treat breast, lung, and prostate cancers in 2018 [13]. JHIS adopted stricter indications for proton and carbon ion therapy ( Table 7).…”
Section: Discussionmentioning
confidence: 99%
“…We compared characteristics, patterns of the HIS, specific indications, and facility qualification for advanced radiation technologies between Korea and Japan, focusing on IMRT, SBRT, intracavitary radiotherapy (ICR), proton, and carbon ion therapy. Furthermore, we compared both nations’ data according to the 2019 guidelines on the application and methods of medical care benefit from the Ministry of Health and Welfare of Korea and the 2020 medical fee points list set by the Ministry of Health, Labor and Welfare of Japan [ 11 - 13 ]. As the cost of insurance treatment between the two countries varies greatly due to social and economic differences, simple comparison of treatment fee was excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Breast-conserving surgery (BCS) followed by adjuvant breast radiotherapy (RT) is the current standard treatment for early-stage breast cancer patients. Addition of adjuvant breast RT after lumpectomy significantly decreased the local recurrence rate and resulted in survival outcomes equivalent to those obtained from radical mastectomy [2][3][4][5]. However, studies with long-term follow-up suggested that breast RT also increased the risk of cardiovascular morbidity [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%